Penggunaan Tanaman Obat Oleh Penduduk Di Beberapa Lokasi Wilayah Indonesia Periode Tahun 2011 Sampai Dengan 2020 - Wahyuli, Nur; Madjid, Baedah; Rompegading, Andi Machmud (Fakultas Kedokteran Universitas Bosowa, 2023)
Medical plants are types of plants which part, all and or plant exudate (cell contents) are used as medicine, ingredients or medicinal ingredients. According to the World Health Organization (WHO) medicinal plants are plants that are used as treatment. The purpose of this study was to the use of medicinal plants by residents in some location in Indonesia from 2011 to 2020. The research method used in this study was a systematic review method with a cross sectional by describing the research results obtained from eleven scientific research articles. The results of research from ten research journals obtained eleven types of medicinal plants based on the types of medicinal plants, parts of medicinal plants used, how to use medicinal plants, and types of use of medicinal plants